Understanding the impact of crosslinked PCL/ PEG/GelMA electrospun nanofibers on bactericidal activity - De Paula, Mirian Michelle Machado; Bassous, Nicole Joy; Afewerki, Samson; Harb, Samarah Vargas [UNESP]; Ghannadian, Paria; Marciano, Fernanda Roberta; Viana, Bartolomeu Cruz; Tim, Carla Roberta; Webster, Thomas Jay; Lobo, Anderson Oliveira (Public Library of Science (PLoS), 2018)
Herein, we report the design of electrospun ultrathin fibers based on the combination of three different polymers polycaprolactone (PCL), polyethylene glycol (PEG), and gelatin methacryloyl (GelMA), and their potential bactericidal activity against three different bacteria Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa), and Methi-cillin-resistant Staphylococcus aureus (MRSA). We evaluated the morphology, chemical structure and wettability before and after UV photocrosslinking of the produced scaffolds. Results showed that the developed scaffolds presented hydrophilic properties after PEG and GelMA incorporation. Moreover, they were able to significantly reduce gram-positive, negative, and MRSA bacteria mainly after UV photocrosslinking (PCL:PEG:GelMa-UV). Furthermore, we performed a series of study for gaining a better mechanistic understanding of the scaffolds bactericidal activity through protein adsorption study and analysis of the reactive oxygen species (ROS) levels. Furthermore, the in vivo subcutaneous implantation performed in rats confirmed the biocompatibility of our designed scaffolds.